1987
DOI: 10.1159/000153691
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism behind the Association between ABO Blood Groups and Gastric Carcinoma

Abstract: It has been hypothesized that the mechanisms behind the association between blood group A and gastric carcinoma is that the carcinoma cells produce an antigen immunologically related to blood group A, which particularly in O-individuals may have a protective effect by preventing the growth and spread of the tumour. The hypothesis predicts that O-individuals would have a longer survival time than A-individuals and that eventually the protective effect in blood group·would be somewhat stronger in women with mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 3 publications
1
8
0
Order By: Relevance
“…The homotypic and heterotypic cell adhesion mediated by interactions of certain blood group carbohydrates with corresponding lectins is a critically important event at the extravasation step of the metastatic cascade when metastatic cancer cells escape from circulation into distant sites of secondary tumor growth. [22] In our study the frequency of blood group "A" was predominant in both leukoplakia and OSMF group.…”
Section: Discussionsupporting
confidence: 52%
“…The homotypic and heterotypic cell adhesion mediated by interactions of certain blood group carbohydrates with corresponding lectins is a critically important event at the extravasation step of the metastatic cascade when metastatic cancer cells escape from circulation into distant sites of secondary tumor growth. [22] In our study the frequency of blood group "A" was predominant in both leukoplakia and OSMF group.…”
Section: Discussionsupporting
confidence: 52%
“…29 Blood group O also appears to exert a protective effect by preventing the growth and spread of tumors and being associated with longer survival times in cancer patients. 30 The following will correlate our finding to, and might explain, the above finding. Thomsen-Friedenreich antigen (TF), which was discovered in the late 1920s, 31 is the core disaccharide structure of ABO blood group (H) substance.…”
Section: Discussionmentioning
confidence: 53%
“…In this study, we also observed that the rate of distant metastasis was significantly higher in male patients with blood type A than those with other blood types. Previous studies also found that blood type O appears to prevent the growth and spread of tumors. The ABO blood group is determined by the expression of A and B antigens on the surface of red blood cells and anti‐A and anti‐B antibodies in the serum.…”
Section: Discussionmentioning
confidence: 81%